THE ROLE OF THE CONSTITUTIONAL COURT AS A POSITIVE LEGISLATOR IN THE FRAMEWORK OF POWER DISTRIBUTION - Vebriani, Anita; Zainuddin, Zainuddin; Nabilah, Wardatun (UIN Mahmud Yunus Batusangkar, 2024)
The central focus of this thesis is to examine the boundaries of the Constitutional Court's authority as a Positive Legislator within the framework of the Doctrine of Power Distribution. The study aims to identify and define the limits of the Constitutional Court's role as a Positive Legislator while exploring its implications within the broader constitutional framework.This research employs a normative juridical (library research) approach with a qualitative typology. Primary data sources include the 1945 Constitution of the Republic of Indonesia, Law Number 24 of 2003 concerning the Constitutional Court, Law Number 7 of 2017 concerning General Elections, and various Constitutional Court decisions. Secondary legal materials, such as relevant books and journals, complement the primary data to provide a comprehensive analysis.The findings of this study reveal two key points. First, regarding the Constitutional Court's decisions with elements of positive legislator authority, cases such as Decision Number 60/PUU-XXII/2024 and Decision Number 90/PUU-XXI/2023 illustrate how the Court's rulings can develop and modify legal norms. These decisions demonstrate that the Constitutional Court, through its role as a Positive Legislator, may issue rulings that adapt laws to societal contexts and needs, provided they remain consistent with the 1945 Constitution of the Republic of Indonesia.Second, concerning the limits of the Constitutional Court's authority, its jurisdiction is explicitly outlined in Article 24C paragraph (1) of the 1945 Constitution and Article 10 paragraph (1) of the Constitutional Court Law. These provisions empower the Court to review laws against the Constitution, adjudicate disputes over the authority of state institutions as defined by the Constitution, resolve cases involving the dissolution of political parties, and settle disputes over election results. In its judicial review capacity, the Constitutional Court traditionally acts as a Negative Legislator by nullifying norms that contradict the Constitution. However, in certain cases, such as Decision Number 90/PUU-XXI/2023, the Court assumes the role of a Positive Legislator by creating or introducing new legal norms, thereby expanding its influence within the legal system.